Assessment of Corneal Endothelium during Continued Organ Culture of Pre-Stripped Human Donor Tissue for DMEK Surgery. (2nd December 2018) - Menzel-Severing, Johannes; Walter, Peter; Plum, Wolfgang J; Kruse, Friedrich E; Salla, Sabine
ABSTRACT: Purpose : To measure corneal endothelial cell (EC) quality and quantity following Descemet membrane (DM) stripping of human donor corneas and continued storage in organ culture medium containing dextran. Methods : DM stripping was performed in 30 organ cultured, corneoscleral discs. Corneas were divided into 3 groups of 10 corneas each. Baseline mean EC density (cells/mm 2 ) was 2, 372 (SD ± 259) in group 1, 2, 540 (SD ± 266) in group 2, and 2, 665 (SD ± 263) in group 3. Following subtotal DM stripping, culture was continued at 31°C for 24 hours (group 1), 72 hours (group 2), and 120 hours (group 3), respectively. EC density was measured before stripping and at the end of culture. At the end of culture, corneal EC morphology was graded using a scoring system and EC viability was measured by detection of adenosine triphosphate. Results : At the end of culture, mean EC density was 2, 159 (SD ± 293) in group 1, 1, 946 (SD ± 182) in group 2, and 2, 047 (SD ± 225) in group 3. This constitutes an EC loss of 9, 1% (SD ± 5, 3%) in group 1, 23, 0 % (SD ± 6, 5%) in group 2, and 22, 7% (SD ± 9, 1%) in group 3 ( p  < 0.001). After completion of follow-up, all groups contained corneas with EC counts < 2, 000 cells/mm 2 . Cell morphology scores did not differ between the three experimental groups. EC viability measurements showed a tendency toward lower readings with extended length of culture. Conclusions : Corneal EC loss does occur following DM stripping and continued organ culture. EC loss increases with storage past 24 hours, but donor corneas may fall below 2, 000 cells/mm 2 independently of storage duration. The use of eye bank prepared donor lamellae for Descemet Membrane Endothelial Keratoplasty (DMEK) may increase patient safety by offering standardized quality control before tissue release.